PEMERIKSAAN KOMPOSISI TUBUH DENGAN METODE BIOIMPEDANCE ANALYSIS DAN PENGUKURAN KADAR ASAM URAT DARAH PADA MASYARAKAT USIA LANSIA - Sugiritama, I.W.; Arijana, I.G.K.K.; Wiryawan, I.G.N.S.; Ratnayanti, I.G.A.D.; Linawati, N.M.; Wahyuniari, I.A.I. (Buletin Udayana Mengabdi; Vol 23 No 3 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i03.p15, 2023)
Studies found that the prevalence of hyperuricemia in the elderly was quite high. Hyperuricemia caused gout arthritis and is also associated with many degenerative diseases. There was a correlation between blood uric acid levels with hypertension, body fat composition, kidney disease, and cardiovascular disease. The purpose of this activity was to determine blood uric acid levels, body fat composition, blood pressure, and body mass index on elderly of Demulih Village. A total of 80 elderly participated in community service activities include of 39 men and 41 women, with an age range from 60 to 80 years. Measurement with bioimpedance analysis tool found 20 percent of respondents are obese, 20 percent overweight, 13.7 percent thin and the rest were normal. Body fat composition analysis found that 51.3 percent was higher than normal. The prevalence of hypertension among the elderly is 50 percent, which comprises hypertension categories 1 and 2, and 26.3 percent were pre-hypertension. Measurement of blood uric acid levels found that as many as 76 percent of the elderly had hyperuricemia. These data indicate that the prevalence of hyperuricemia and other cardiovascular disease risk factors is quite high in the elderly in Demulih Village. Keywords: blood uric acid, blood pressure, BMI, body fat composition, eldery